2020
DOI: 10.7189/jogh.10.010411
|View full text |Cite
|
Sign up to set email alerts
|

High value of rapid diagnostic tests to diagnose malaria within children: A systematic review and meta-analysis

Abstract: High value of rapid diagnostic tests to diagnose malaria within children: A systematic review and meta-analysis Background Children aged under five years accounted for 61% of all malaria deaths worldwide in 2017, and quicker differential diagnosis of malaria fever is vital for them. Rapid diagnostic tests (RDTs) are strips to detect Plasmodium-specific antigens promptly and are helpful in resource-limited areas. Thus, our aim is to assess the diagnostic accuracy of RDTs for malaria in children against the gold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 84 publications
(60 reference statements)
1
10
0
Order By: Relevance
“…At the same time, with the increase of age, the diagnostic competency of microscopy technicians will decrease. In contrast, Rapid Diagnostic Test (RDT) is more convenient and faster than plasmodium microscopy in the areas lacking equipment, technicians, and technologies, and has lower requirements on the technicians' competence (33,39), so is more suitable to be widely used in primary health institutions in Chongqing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, with the increase of age, the diagnostic competency of microscopy technicians will decrease. In contrast, Rapid Diagnostic Test (RDT) is more convenient and faster than plasmodium microscopy in the areas lacking equipment, technicians, and technologies, and has lower requirements on the technicians' competence (33,39), so is more suitable to be widely used in primary health institutions in Chongqing.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the number of imported cases of P. ovale malaria cases has increased year on year ( 20 , 29 , 30 ), which is related to the establishment of malaria reference laboratories nationwide to carry out PCR reviews for each reported case since the implementation of the malaria elimination action plan. Compared with other detection methods, PCR detection can more accurately distinguish various types of plasmodium species ( 25 , 27 , 31 – 33 ). In 2012, the malaria reference laboratory was established in Chongqing CDC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, RDT is suitable for primary health care institutions with limited facilities and unskilled staff. However, they may also fail to accurately diagnose for cases with low parasitaemia, and false positives are possible due to cross reactions [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…RDTs can detect only one species ( Plasmodium falciparum [ P. f. ]) or multiple species ( P. vivax , P. malariae and P. ovale ) [ 9 11 ]. RDTs have much shorter testing time, user-friendly testing procedure, and similar accuracy compared to microscopy [ 10 , 12 – 15 ]. Thus, RDT is particularly appropriate in improving the accessibility and efficiency of malaria testing for febrile patients at the grassroot level [ 16 ].…”
Section: Introductionmentioning
confidence: 99%